Investigation of Noise Pollution of Electrical Diesel Generators in Duhok City/ Kurdistan of Iraq - MAHAMMED, MANAF A.; KOCHERY, FARIS A.; ABDULKHALIQ, MOHAMMED S. (Science Journal of University of Zakho, 2013)
The City of Duhok, Kurdistan region of Iraq, whilst has been subjected to persistent fast development and urbanization and expansion of economy, travel and tourism, it is still suffering from the shortage of public electricity supply since 1990. This leads to widely depending on diesel electricity generators. This study investigates diesel generators noise pollution in Duhok city. An empirical correlation formula was deduced for the mean noise level of 30 diesel generator sites as a function of distance for the 50 meters range, and then this correlation is extrapolated up to 80 m from the sites. The results showed that the measured mean noise level at 50 m from the generator sites was 74.86 dB(A) which is higher than the permissible noise level for residential and commercial areas that are 55 dB(A) and 65 dB(A) respectively, while it is near the industrial areas which equals 75 dB(A). On making the extrapolation to the empirical formula to compare distance up to 80 m from the sites, the extrapolated mean noise level reduced to 71.1 dB(A) which is still beyond the permissible noise level for residential and commercial areas.